Standing at the Edge of Reconstructable Transmission-History: Signs of a Secondary Sabbath-Oriented Stratum in Genesis 1:1-2:3 - Carr, David McLain (Vetus Testamentum, 2020)
Past studies of the formation of Genesis 1 have varied between a hypothesis of Word' and Act' Strata, the idea of a secondary Sabbath-oriented (Holiness) Stratum, and Arguments for literary unity. This article gathers older and new arguments to advance the hypothesis of a secondary Sabbath-oriented stratum.